Ability of combinations of cash flow components to predict financial distress - Kordestani, Gholamreza; Bakhtiari, Mehrdad; Biglari, Vahid (Business: Theory and Practice, 2011)
The aim of this research is to provide a model that predicts company’s financial distress on the basis of the operational, investment and financing components of its cash flow statement. To prevent bankruptcy and its negative consequences that among them are abuse of creditors, investors, management and employees’ right, the prediction of financial distress and its probable consequence such as bankruptcy is essential. To serve this purpose, for the research 70 reliable firm-years and 70 distressed firm-years within the years 1995 to 2008 were selected from Tehran stock exchange. Considering the information that is reflected in the cash flow statement, the viability of financial distress prediction was examined. The result of chi-square test shows that there is significant difference in incidence rate of financial distress among the companies with different cash flow composition in one, two and three years before distress. In other words, the financial distress can be predicted on the basis of the contents and composition of the cash flow statement.